2020
DOI: 10.1155/2020/2032679
|View full text |Cite|
|
Sign up to set email alerts
|

KIF20A Predicts Poor Survival of Patients and Promotes Colorectal Cancer Tumor Progression through the JAK/STAT3 Signaling Pathway

Abstract: Kinesin family member 20A (KIF20A) has been recently reported to be upregulated and associated with increased invasiveness and metastasis in several malignancies. However, the role of KIF20A in colorectal cancer (CRC) is still unclear. This study is aimed at investigating the potential roles of KIF20A in the development of CRC. The results of bioinformatics analysis, immunohistochemical staining, and Western blot analysis showed that KIF20A was overexpressed in CRC tissues compared with adjacent normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…In addition, KIF23 and KIF20A, as members of the kinesin-6 subfamily, have similar functions in maintaining normal cell division 31 . Our previous studies have shown that high expression of KIF20A can significantly promote the proliferation of colorectal cancer, and it is related to the poor prognosis of colorectal cancer patients 32 . Therefore, we speculate that KIF23 may play a similar role as KIF20A in colorectal cancer.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, KIF23 and KIF20A, as members of the kinesin-6 subfamily, have similar functions in maintaining normal cell division 31 . Our previous studies have shown that high expression of KIF20A can significantly promote the proliferation of colorectal cancer, and it is related to the poor prognosis of colorectal cancer patients 32 . Therefore, we speculate that KIF23 may play a similar role as KIF20A in colorectal cancer.…”
Section: Discussionmentioning
confidence: 98%
“…For example, activation of the TGF-β/Smad2 signaling pathway mediated by HMMR contributes to the chemoresistance of gastric cancer ( 41 ). KIF20A maintains a set of malignant characteristics in colorectal cancer by activating the JAK/STAT3 pathway ( 42 , 43 ). However, little is known about GPR87, PGM2L1, and ANKZF1 in PCa.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, leptin stimulates prostate cancer cell proliferation and migration through STAT3 (Gorrab et al, 2020). In addition, KIF20A knockout reduces colorectal cancer cell proliferation and migration by inhibiting the JAK/STAT3 pathway (Zhang et al, 2020). On the other hand, some studies illustrated that the Hoveniae Semen Seu Fructus Ethanol extract exhibits anti-inflammatory activity via MAPK, AP-1, and STAT in lipopolysaccharide (LPS)-stimulated RAW 264.7 and mouse peritoneal macrophages (Jeong et al, 2019).…”
Section: Discussionmentioning
confidence: 99%